Changes in telomere length and telomerase activity in human bronchial epithelial cells induced by coal tar pitch extract. Issue 6 (29th September 2015) - Feng, Feifei; Yang, Yongli; Li, Zhitao; Song, Jinyan; Zhu, Hansong; Wang, Lixia; Zhao, Yong; Xu, Dong; Wu, Yongjun; Wu, Yiming; Wang, Wei
Graphical Abstract: Abstract: Coal tar pitch is a confirmed human carcinogen and is composed mainly of polycyclic aromatic hydrocarbons. Coal tar pitch extract (CTPE) is toxic to humans and animals due to its ability to induce carcinogenesis, teratogenesis, and mutagenesis. The aim of this study was to explore the effects of CTPE on BEAS-2B cells in vitro and the mechanism responsible for the changes in telomere length and telomerase activity in lung cancer. In this study, BEAS-2B cells were divided into three groups: the blank, DMSO and CTPE groups; we found that the telomere length shortened significantly and telomerase activity increased in cells in the CTPE group at passages 20 and 30 compared to cells in the CTPE group at passage 10. In addition, the gene and protein expression levels of POT1, TRF1 in BEAS-2B cells in the CTPE group at passages 20 and 30 were significantly reduced, and the gene and protein expression levels of TRF2 were increased, compared to those in cells in the CTPE group at passage 10. CTPE can shorten telomere DNA and increase telomerase activity in human bronchial epithelial cells. The phenomenon of chromosomal instability may be related to the lower expression of POT1 and TRF1 and the higher expression of TRF2.